Vaginal progesterone as maintenance treatment after an episode of preterm labour (PROMISE) study: a multicentre, double‐blind, randomised, placebo‐controlled trial. (30th March 2016) - Palacio, M; Cobo, T; Antolín, E; Ramirez, M; Cabrera, F; Mozo de Rosales, F; Bartha, JL; Juan, M; Martí, A; Oros, D; Rodríguez, À; Scazzocchio, E; et al.
Abstract : Objective: To evaluate whether maintenance treatment with vaginal progesterone after an arrested preterm labour reduces the incidence of preterm delivery. Design: Multicentre, randomised, double‐blind, placebo‐controlled trial. Setting: Twelve tertiary care centres in Spain. Population: A total of 265 women with singleton pregnancy, preterm labour successfully arrested with tocolytic treatment, and cervical length of <25 mm. Methods: Randomisation was stratified by gestational age (from 24.0 to <31.0 weeks of gestation and from 31.0 to <34.0 weeks of gestation) and centre. Patients were randomly assigned, in a 1 : 1 ratio, to either daily vaginal capsules of 200 mg progesterone or placebo until delivery or 36.6 weeks of gestation, whichever occurred first. Main outcome measures: Primary outcome was delivery before 34.0 and 37.0 weeks of gestation. Secondary outcomes were discharge‐to‐delivery time, readmissions because of preterm labour, emergency service use, and neonatal morbidity and mortality. Results: From June 2008 through June 2012, 1419 women were screened: 472 met the inclusion criteria and 265 were randomised. The final analysis included 258 women: 126 in the progesterone group and 132 in the placebo group. There were no significant differences between the progesterone and placebo groups in terms of delivery at <34 weeks of gestation [9/126 (7.1%) versus 10/132 (7.6%), P =  0.91] or <37 weeks of gestation [36/126 (28.6%) versus 29/132 (22.0%), P  = 0.22]. There were no differences observed between groups when considering the two strata of gestational age at inclusion. Conclusions: A maintenance treatment of 200 mg of daily vaginal progesterone capsules in women discharged home after an episode of arrested preterm labour did not significantly reduce the rate of preterm delivery. Tweetable abstract: Maintenance progesterone in 258 women after arrested PTL showed no benefit. Tweetable abstract: Maintenance progesterone in 258 women after arrested PTL showed no benefit.